Analisis Kinerja Pegawai Pejabat Pelaksana Teknis Kegiatan (PPTK) Melalui Fungsi Kepemimpinan, Budaya Organisasi Dan Kompetensi Dilingkungan Pemda Kabupaten Bandung - Makbul Mansyur (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
Employee performance in the government environment is the spearhead for the State to provide the excellent service. This study aims to determine the performance of employees who are influenced by the leadership function, organizational culture and competence possessed by the employees. Research method of this study is the quantitative approach with a sample of local government employees. The results of the study show that employee performance is proven to be influenced by the leadership functions, organizational culture and competence.